Splicing therapeutics for patients affected by lysosomal storage disorders - Matos, Liliana (2018)
In this study, we have used a modified U1 snRNA that completely matches the splice donor site of HGSNAT gene exon 2, which corrected the effect of the common 5’ splice site mutation c.234+1G>A in Mucopolysaccharidosis IIIC. In another approach using an antisense oligonucleotide (AO) we have succeeded in the correction of the c.66G>A splicing mutation in CSTB gene (Unverricht–Lundborg disease). Besides that, we have performed the functional analysis of some IDS gene splicing mutations (Mucopolysaccharidosis II) and used AOs to exploit an alternative therapy for one of those mutations (c.1122C>T on exon 8).